Assessing validity and reliability of a new tool: the ECSQ (Endoscopy Customer Satisfaction Questionnaire) in Italian for customer satisfaction in digestive endoscopy - Minciullo, A.; Tartaglini, D.; Colombo, B.; Filomeno, L.; Di Muzio, M. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The European Society of Gastrointestinal Endoscopy and the American Society for Gastrointestinal Endoscopy recommend the identification of quality indicators for endoscopy services, including patient satisfaction. Patients happy with the treatment received will be more willing to participate in screening programs and more adherent to the indications received from the doctor. The aim of this study is to validate the Endoscopy Customer Satisfaction Questionnaire in Italian, in order to have a valid and reliable tool that can allow each patient to fully describe their experience in digestive endoscopy services. Methods. The validation of the questionnaire was carried out through a a monocentric cross-sectional study, in the endoscopy service of the Campus Bio-Medico University Hospital in Rome between August and September 2020. Results. A total of 155 patients underwent an endoscopy. The mean age of the sample was 56.21 years (SD ± 14.136) with 46.5% male and 53.5% female. The analysis of the validity and reliability of the questionnaire was ensured through the finding of an average value of 0.944 for Cronbach’s α. Conclusion. From the analysis of the results, we can therefore believe that the Italian version of the Endoscopy Customer Satisfaction Questionnaire is to be considered valid and reliable for measuring patient satisfaction, allowing them to express their point of view.